Proinsulin and heat shock protein 90 as biomarkers of beta-cell stress in the early period after onset of type 1 diabetes - Watkins, Renecia A.; Evans-Molina, Carmella; Terrell, Jennifer K.; Day, Kathleen H.; Guindon, Lynette; Restrepo, Ivan A.; Mirmira, Raghavendra G.; Blum, Janice S.; DiMeglio, Linda A. (Translational research : the journal of laboratory and clinical medicine, 2016)
Rapid evaluation of therapies designed to preserve β cells in persons with type 1 diabetes (T1D) is hampered by limited availability of sensitive β-cell health biomarkers. In particular, biomarkers elucidating the presence and degree of β-cell stress are needed. We characterized β-cell secretory activity and stress in 29 new-onset T1D subjects (10.6 ± 3.0 years, 55% male) at diagnosis and then 8.2 ± 1.2 weeks later at first clinic follow-up. We did comparisons with 16 matched healthy controls. We evaluated hemoglobin A1c (HbA1c), β-cell function (random C-peptide [C] and proinsulin [PI]), β-cell stress (PI:C ratio), and the β-cell stress marker heat shock protein (HSP)90 and examined these parameters' relationships with clinical and laboratory characteristics at diagnosis. Mean diagnosis HbA1c was 11.3% (100 mmol/mol) and 7.6% (60 mmol/mol) at follow-up. C-peptide was low at diagnosis (P < 0.001 vs controls) and increased at follow-up (P < 0.001) to comparable with controls. PI did not differ from controls at diagnosis but increased at follow-up (P = 0.003) signifying increased release of PI alongside improved insulin secretion. PI:C ratios and HSP90 concentrations were elevated at both time points. Younger subjects had lower C-peptide and greater PI, PI:C, and HSP90. We also examined islets isolated from prediabetic nonobese diabetic mice and found that HSP90 levels were increased ∼4-fold compared with those in islets isolated from matched CD1 controls, further substantiating HSP90 as a marker of β-cell stress in T1D. Our data indicate that β-cell stress can be assessed using PI:C and HSP90. This stress persists after T1D diagnosis. Therapeutic approaches to reduce β-cell stress in new-onset T1D should be considered.